From Speaking Anxiety to Communicative Agency: Reconstructing EFL Learners’ Experiences of Participation in English-Speaking Classrooms : Penelitian - Khusnul Yatima; Delvia Muharramah (Jurnal Pustaka Cendekia Pendidikan, 2026)
Speaking anxiety remains a persistent affective challenge in English as a Foreign Language (EFL) classrooms, particularly when learners are required to participate orally, respond spontaneously, or perform in front of peers. Previous studies have predominantly examined speaking anxiety as a psychological barrier associated with reduced willingness to communicate and limited oral participation. However, less attention has been given to how learners actively negotiate anxiety and develop communicative agency within classroom interaction. This study aims to explore EFL learners’ experiences of speaking anxiety and examine how they negotiate anxiety, construct participation, and develop communicative agency in English-speaking classrooms. A qualitative phenomenological design is proposed to capture learners’ lived experiences. Data are collected through semi-structured interviews, classroom observations, reflective journals, and selected speaking-task recordings. The data are analyzed thematically through iterative coding, categorization, interpretation, and cross-source comparison. The analytical framework focuses on five dimensions: experiences of anxiety, sources of anxiety, patterns of withdrawal and participation, self-regulatory and interpersonal strategies, and the emergence of communicative agency. The study is expected to demonstrate that speaking anxiety should not be conceptualized solely as an individual psychological deficit but as a dynamic experience shaped by linguistic competence, fear of negative evaluation, classroom interaction, teacher practices, peer relationships, and perceived opportunities for participation. The study further conceptualizes communicative agency as an emergent capacity through which learners make strategic decisions to initiate, sustain, modify, or reclaim participation despite experiencing anxiety. The findings are expected to contribute to EFL pedagogy by shifting the pedagogical emphasis from merely reducing anxiety toward creating classroom ecologies that support learner agency, psychological safety, strategic participation, and meaningful English communication.